Effects of carbon quantum dot-chitosan coating on preservation of fresh-cut shiitake mushroom - YANG Na; WEI Qi-min; YANG Wei-ling; HUANG Qun (Shipin yu jixie)
Objective: In order to improve freshness preservation quality of the fresh-cut shiitake mushroom. Methods: Carbon quantum dots were synthesized from dragon fruit peel and ethylenediamine, and characterized for stability and toxicity. Fresh-cut shiitake mushrooms were studied, and stored at 4 ℃ for 10 d after coating with 0.0, 1.5, 3.0 and 4.5 mL/100 mL carbon quantum dots-chitosan （N-CDs/CH） for preservation treatment. During the period of preservation, the weight loss, color difference, soluble solids and polyphenol oxidase were measured every 24 h to evaluate the preservation effect of the composite films. Results: The synthesized N-CDs had the typical characteristics, which had good fluorescence stability, hydroxyl and amino groups on outer surface, and no cytotoxicity. After fresh-cut shiitake mushrooms were treated with different concentrations of N-CDs/CH until the 10th day of storage, 4.5 mL/100 mL N-CDs/CH coating group had weight loss of 3.31%, coloration of 10.32, soluble solids of 4%, and polyphenol oxidase （PPO） activity of 104.65 U/(kg·s), all of which were significantly better than the blank group and other treatment groups （P＜0.05）. Conclusion: The preservation effect at the 4.5 mL/100 mL of N-CDs/CH coating was significantly better than that of blank and others （P＜0.05）. N-CDs/CH coating inhibited water loss and PPO activity, improved color and enhanced the preservation quality of fresh-cut shiitake mushroom.